Grounded Series/Parallel RC Impedance Simulators with a Single VDBA - Pitchayanin Moonmuang; Tattaya Pukkalanun; Masaaki Fukuhara; Worapong Tangsrirat (My University, 2023)
This article presents grounded RC series/parallel impedance simulator circuits employing a single voltage differencing buffered amplifier (VDBA) as an active element. The proposed RC series impedance simulator consists of one capacitor and one resistor, while the proposed grounded RC parallel type requires only a single capacitor as a passive element. The simulated equivalent resistance and capacitance values can be tuned electronically through the transconductance gain of VDBA device which can be adjusted by means of the external biasing current. The performance validation of the proposed circuits including the resonant circuit application is proved by simulation results via PSPICE software based on TSMC $0.25-\mu \mathfrak{m}$ CMOS technology.
Keywords: Radio Frequency Integrated Circuit Design; Analog and Mixed-Signal Circuit Design; Energy Harvesting in Wireless Networks